Adapting to Climate Change Through Conservation Agriculture: A Gendered Analysis of Eastern Zambia - Umar, Bridget Bwalya (Frontiers in Sustainable Food Systems, 2021)
This study explored the use of conservation agriculture (CA) as a climate adaptation strategy among smallholder farmers in Eastern Zambia. Using 761 household interviews and 33 focus group discussions (FGDs) with smallholder farmers from six districts, data was collected on how smallholder farmers in the region experience climate change, what CA practices they had adopted, and benefits and challenges associated with CA practice. Results show that men and women farmers had similar experiences of climate change, namely late onset of a shortened rainy season, intra-seasonal drought and higher temperatures. Farmers’ perceptions of gender-mediated effects of climate change had important nuances. The three most cited effects of climate change on women mentioned by women were lower crop yields, outbreaks of armyworms and reduced livestock fodder. The men thought women were most affected by increased hunger, lower crop yields and reduced domestic water sources. According to the women FGDs, men were most affected through reduced crop yields, increases in livestock diseases and increased hunger. The men self-reported reduced crop yields, reduced water for livestock and outbreaks of armyworms. Both men and women saw CA as having climate change adaptation benefits. For the women, men most benefitted from CA through the high moisture holding capacity of basins, higher crop yields and reduced labour requirements through use of oxen ripping. The men most appreciated the high crop yields, improved soil fertility and reduced costs as less fertilizer is used. The women cited the high moisture holding capacity of basins, high crop yields and improved soil fertility as benefits they most commonly derived from CA, while the men thought the women most benefitted from CA through the higher crop yields, improved soil fertility and crop tolerance to droughts. The study concludes that there is room for CA to serve as a climate smart agricultural system for both men and women smallholder farmers in Eastern Zambia. However, this will require addressing important challenges of high weed pressure, high labour demands, and low access to manure, and CA farming implements. The CA package for Zambia should include access to timely climate information and climate informed crop choices.